Compressible turbulence with slow‐mode waves observed in the bursty bulk flow of plasma sheet. Issue 5 (12th March 2016) - Wang, Tieyan; Cao, Jinbin; Fu, Huishan; Meng, Xuejie; Dunlop, M.
Abstract: In this paper, we report the evidence of compressible turbulence with slow‐mode waves in a bursty bulk flow of plasma sheet. This compressible turbulence is characterized by a multiscale (1–60 s) anticorrelation between plasma density and magnetic field strength. Besides, the magnetic compressibility spectrum stays nearly constant at all the measured frequencies. Furthermore, the turbulence energy distributions are anisotropic with k ⊥  >  k //, and the dispersion relation is consistent with slow‐mode prediction. The fluctuations of density and magnetic field have similar double slope spectrum and kurtosis. These results suggest that the slow waves are involved in the intermittent turbulence cascade from MHD to ion kinetic scales, which may have significant implications for the energy transfer in the plasma sheet. Key Points: Multiscale anticorrelation of n and B is found in the plasma sheet compressible turbulence Slow‐mode waves are found from MHD scales to ion kinetic scale Both n and B fluctuations have similar intermittent behavior